OPTIMIZATION OF PCR PROTOCOL TO IDENTIFY THEILERIA ANNULATA - Kuibagarov , M.A.; Makhamed , R.; Lider , L.A.; Abdrakhmanov , S.K.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2019)
Theileriosis is a blood-parasitic disease of domestic and wild animals caused by Theileria annulata. Although the disease course varies in severity, it is most often fatal. Theileriosis is endemic to the southern regions of Kazakhstan, and the main means of combatting the disease are accurate diagnosis and appropriate treatment. In this regard, the timely detection of infection is a critical step in initiating preventive measures. Polymerase chain reaction (PCR) allows for the detection of latent carriage of the parasite with higher sensitivity than classical microscopic detection. The aim of this work was to determine the optimal parameters of PCR for detecting T. annulata DNA using the enolase (ENO) gene as a diagnostic target. Selected primers at the estimated rates of the PCR revealed the presence of T. annulata in 4 of 18 DNA samples isolated from ticks. Subsequent optimization of the conditions increased the efficiency of PCR. The specificity of the developed protocol was confirmed by direct sequencing of known positive samples. This optimized method is expected to improve diagnosis at an early stage of infection to allow for timely treatment and a better outcome.